Evaluating a symptom‐triggered gastric residual volume policy in a surgical trauma intensive care unit: Simple and safe. (24th March 2021) - Prest, Phillip J.; Reath, Jessica Justice; Bell, Nathaniel; Rabieh, Mona; Moore, Aaron; Jones, Mark; Watson, Christopher; Bynoe, Raymond
Abstract: Background: Routine checking of gastric residual volumes (GRVs) during enteral feeding within surgical trauma intensive care units (STICUs) is a common practice. However, data on the necessity of this practice and its impact on nutrient delivery are limited. We aim to study the association between the replacement of a routine GRV (rGRV) policy with a triggered GRV (tGRV) policy and the safe achievement of daily nutrition goals. Methods: We prospectively collected data on patients after we instituted a tGRV policy and compared them with a historical cohort of patients who had rGRV assessments in our STICU at a level 1 trauma center. The primary end point was achieving 80% of prescribed nutrient goals. Secondary end points included aspiration pneumonia, witnessed emesis, and glycemic control. Results: A total of 145 patients accounting for 1405 STICU days were treated under the tGRV policy, and 156 patients accounting for 1694 STICU days were treated under the rGRV policy. There were no statistically significant differences between the tGRV and rGRV groups with regard to the proportion of days meeting or exceeding protein (56.7% vs 56.2%) or calorie (56.4% vs 56.0%) goals. After adjusting for in‐hospital deaths, injury severity score, complications, and STICU time, the predictive margins for meeting caloric and protein goals were higher among the tGRV patients (57% vs 56%), but these differences were not statistically significant. Conclusion: A tGRV policy did not change protein or calorie delivery among patients or increase the risk of emesis compared with traditional monitoring methods.